2004
DOI: 10.1063/1.1817999
|View full text |Cite
|
Sign up to set email alerts
|

Driving force and composition for multicomponent gas hydrate nucleation from supersaturated aqueous solutions

Abstract: The expression for driving force is presented for multicomponent gas hydrate nucleation in an aqueous phase. The derivation includes working equations for predicting the composition of a hydrate nucleus. The results for driving force in multicomponent systems show a significant effect of the composition of the hydrate nucleus. All past work assume a fixed composition based on the three-phase equilibrium point independent of subcooling and supersaturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 16 publications
3
37
0
Order By: Relevance
“…(6) to multicomponent systems. As highlighted by Anklam and Firoozabadi (2004), the assumption that the composition of the nucleated hydrate is constant and equal to the one at the three-phase equilibrium point for any supersaturation may not be valid if the operating conditions are far away from the gas-liquid-hydrate equilibrium conditions. With the aim of eliminating this limitation, these authors developed a new expression for hydrate nucleation.…”
Section: Modelling Of Hydrate Nucleationmentioning
confidence: 97%
See 1 more Smart Citation
“…(6) to multicomponent systems. As highlighted by Anklam and Firoozabadi (2004), the assumption that the composition of the nucleated hydrate is constant and equal to the one at the three-phase equilibrium point for any supersaturation may not be valid if the operating conditions are far away from the gas-liquid-hydrate equilibrium conditions. With the aim of eliminating this limitation, these authors developed a new expression for hydrate nucleation.…”
Section: Modelling Of Hydrate Nucleationmentioning
confidence: 97%
“…For practical purposes, such as natural gas storage, when different hydrate-forming gases are present, expressions valid for multicomponent systems are required. Upon representing the formation of a unit cell of a multicomponent hydrate by the general formula: Anklam and Firoozabadi (2004) demonstrated that, for isothermal operation, with the assumptions of gas-saturated liquid, unitary activity coefficient for water in the solution, negligible compressibility coefficients for liquid and hydrate phases and a fixed composition for the hydrate, independent of supersaturation and equal to the equilibrium one, the driving force for hydrate nucleation is given by…”
Section: Modelling Of Hydrate Nucleationmentioning
confidence: 99%
“…While hydrate nucleation and formation have been described in the literature [7][8][9][10][11][12][13][14][15][16] , there are relatively few studies on hydrate adhesion. Most adhesion studies to date have used a micromechanical adhesion testing apparatus to measure adhesion forces between hydrate particles, or between hydrate and ice particles.…”
Section: Introductionmentioning
confidence: 99%
“…The time of gas hydrates formation depends on many factors, such as various gases concentration in the gas mixture, water content, presence of dust particles in the gas, moisture content in the gas, rate of cooling, speed of diffusion, thermodynamic driving force (Kashchiev & Firoozabadi, 2002;Anklam & Firoozabadi, 2004;Mottahedin, Varaminian, & Mafakheri, 2011;Fandiño & Ruffine, 2014).…”
Section: Utilization Of Coalbed Methanementioning
confidence: 99%